Review: Peter McLaren, (2015) Pedagogy of Insurrection (Concept: The Journal of Contemporary Community Education Practice Theory, 2017)
When Stalin and the Politburo of the Communist Party of the Soviet Union saw Shotakovich’s Lady Macbeth at the Moscow Bolshoi Theatre in 1936 they got so upset and finally outraged that the opera was crushed and condemned the next morning in the Party’s official newspaper Pravda. The second blast came a decade or so later in the Zhdanov Resolution, in which the famous composer was accused of rotten formalism. Shostakovich learnt the hard lesson and thereafter composed his symphonies - so to speak - for Stalin and the Politburo. Eventually he was forced to join the Communist Party and pretend to follow its doctrines.